Influence of devolatilisation conditions on char chemical structure and intrinsic reactivity - Wang, M.; Roberts, D.; Kochanek, M.; Harris, D.; Chang, L.; Li, Chun-Zhu (International Pittsburgh Coal Conference, 2013)
Raman spectroscopy has been widely used to study chemical structures of chars and further our understanding of their behaviour under combustion and gasification conditions. This paper explores the impact of devolatilisation conditions (heating rate, temperature, pressure and residence time) on char intrinsic reactivity. Chars were made at 900°C and 1100°C using slow (0.1°C/s) and rapid (1000°C/s) heating rates, and 1 bar and 20 bar pressure. These chars were characterised for their surface area (using N 2 and CO2 adsorption), and Raman spectra were used to understand the impacts of devolatilisation conditions on ratios of small to large features of the carbon matrix. The intrinsic reactivity behaviour of these same chars was then determined using a pressurised thermogravimetric analyser (TGA) Overall Raman intensities of slow heating rate, long residence time chars were significantly less than those for chars made under fast heating rates with shorter residence times. Increasing pyrolysis temperature also led to a reduction in total peak area for chars from both coals, giving some insights into the effect of temperature and residence time on chemical functional groups present in char. There is also a greater ratio of small to large aromatic ring structures in the lower temperature chars, and in the chars made with faster heating rates and shorter residence times.These effects on the ratios of small to large structures are shown to be consistent with their impacts on intrinsic reactivity. The effects of devolatilisation pressure were less clear. Increasing pressure has led to a decrease in total Raman intensity for chars from the lignite, and an increase for chars from the bituminous coal. This was accompanied by some impacts of devolatilisation pressure on reactivity, whereby the higher-pressure char was more reactive (on an apparent and intrinsic basis) than the atmospheric pressure char. Clearly, the effects of pyrolysis pressure are complex, and warrant further work.